Determinant of income inequality in Malaysia: a time series analysis / Nur Ainina Kamarudin - Kamarudin, Nur Ainina (Faculty of Business and Management, 2017)
The objective of the present study is to examine the factor that most affected on income inequality in Malaysia for the period between 1970 and 2014 using times series framework. To answer 4 objectives under this investigation, through multiple linear regressions, GDP and FDI show that there are no significant relationships with income inequality whereby import and export shows otherwise. Regarding this research, the most affected on income inequality in Malaysia is import which has lowest p-value in multiple linear regression tests.